2020
DOI: 10.1039/c9sm02277e
|View full text |Cite|
|
Sign up to set email alerts
|

Spatially heterogeneous dynamics of cells in a growing tumor spheroid: comparison between theory and experiments

Abstract: Spatially heterogenous dynamics inside a growing tumor spheroid.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…defined by sub-diffusive movement with an intermediate time slowdown, as observed in colloidal systems); ( Kegel and van Blaaderen, 2000 ; Weeks et al, 2000 ; Figure 1E,F , blue). The juxtaposition of liquid- and glass-like motion along a single cell-cell junction was interesting, because while fluid-to-glass phase transitions are known features at tissue-level length scales ( Angelini et al, 2011 ; Bi et al, 2015 ; Malmi-Kakkada et al, 2018 ; Sinha et al, 2020 ), such transitions have not been reported at sub-cellular length scales during morphogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…defined by sub-diffusive movement with an intermediate time slowdown, as observed in colloidal systems); ( Kegel and van Blaaderen, 2000 ; Weeks et al, 2000 ; Figure 1E,F , blue). The juxtaposition of liquid- and glass-like motion along a single cell-cell junction was interesting, because while fluid-to-glass phase transitions are known features at tissue-level length scales ( Angelini et al, 2011 ; Bi et al, 2015 ; Malmi-Kakkada et al, 2018 ; Sinha et al, 2020 ), such transitions have not been reported at sub-cellular length scales during morphogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…1E, F, blue ). The juxtaposition of liquid- and glass-like motion along a single cell-cell junction was interesting, because while fluid-to-glass phase transitions are known features at tissue-level length scales (Angelini et al, 2011; Bi et al, 2015; Malmi-Kakkada et al, 2018; Sinha et al, 2020), such transitions have not been reported at sub-cellular length scales during morphogenesis. To confirm this surprising result, we applied four additional physical metrics, the Van Hove function, the velocity auto-correlation function, the self-overlap parameter, and the fourth order susceptibility, χ 4 ( t ) ( SI sections 2-4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additional complexities on fusion dynamics could arise as cells enter a pressuredependent dormant state, increasing tissue heterogeneity. For example, the increased pressure in the core of tumor spheroids results in a jammed stage with dormant cells, while cells at the periphery grow and motility is super-diffusive [36].…”
Section: Discussionmentioning
confidence: 99%